A study of lapping parameters to reduce polishing time of optical glass - Elshwain, Amad Alddein (2007)
Machining of hard and brittle material always pose problems such as rough surface, cracks, sub-surface damage and residual stress mainly due to its brittle nature. In recent year researchers and manufactures have put in of lot effort to design and fabricate highly precise device to achieve low tolerance, better surface finish and low sub-surface damage at reduced cost. In this study ultrasonic grinding was used to grind flat surface on the BK7 glass. Only feed rate was varied during grinding, ie. 0.5, 1.5, 2.5, and 3.5mm/min while other parameters such depth of cut (5Âµm), frequency (20kHz) and spindle speed (1000rpm) were fixed. The four ground samples were lapped at various table speeds and followed by polishing operations at fixed conditions. Surface roughness and surface morphology of the samples were evaluated after each process. It is found that surface roughness increases when the feed rate increased. Higher lapping speed (50rpm) remove material faster and fines better surface finish than lower speeds. Saturation point of surface roughness occurs at 10 minutes lapping time. The finest polishing surface achievable using less rigid machine was 38nm. It is expected lower Ra could be obtained after polishing if the same lapping and polishing machine is used for both processes.